Waste Not, Want Not: How Utilities Can Help Consumers Save Energy - Hemmes, Frank; Papyrakis, Elissaios; van Beukering, Pieter (Consilience, 2012)
Energy consumption by households plays an important part in the creation of greenhouse gasses and thus contributes to climate change. Decreasing this consumption can thus help to reduce emissions. In this article, we look at means to assist consumers in controlling their energy use, by giving them customized feedback on their electricity meter readouts. During a one-month test, customers of Dutch energy utility Greenchoice could upload their electricity meter readouts and receive information to monitor their consumption. Feedback on consumption is thought to stimulate consumers to use less energy. The results of the experiment support this theory, as participating customers consumed 6-7 percentage points less electricity compared to non-participants.